Respuesta :

Step-by-step explanation:

1) = {5(x+y)} - 2x

= 5x + 5y - 2x

= 3x + 5y

2)= {2(p×q)} + (p×q)

= (2p×2q)+ p×q

= 4pq + pq

= 5pq

3)= 6a + (8b + 2a)

= 8a + 8b

= 8(a+b)

4)= 3x² + ( x²+7x)

= 4x² + 7x

= x(4x+7)

Answer:

Step-by-step explanation:

72) 5*(x +y) - 2x

  = 5x + 5y - 2x  {Distributive property}

  = (5x - 2x) + 5y    {Combine like terms}

  = 3x + 5y

73) 2*(pq) + pq

   = 2pq + pq     {Combine like terms}

   = 3pq

74) 6a + (8b + 2a)

     = 6a + 2a + 8b   {Combine like terms}

    = 8a + 8b

75) 3*x² + (x² + 7x)

   = 3x² + x² + 7x   {Combine like terms}

   = 4x² + 7x

ACCESS MORE